Analisis Perubahan Penggunaan Lahan Kota Kupang Nusa Tenggara Timur Tahun 2010-2018 : Studi Kasus di Kecamatan Kelapa Lima, Oebobo, dan Kota Lama - Angin, Ignasius Suban; Sunimbar, Sunimbar (geoedusains: Jurnal Pendidikan Geografi, 2021)
Urban land use is one of the important factors in urban environmental planning and modeling. Recent developments also show that Remote Sensing has been accepted as one of the main tools for information extraction and mapping. Extraction of land use information based on Remote Sensing includes visual interpretation and digital interpretation. This study aims to assess the ability of SAS Planet High Resolution Satellite Imagery in mapping land use, and obtaining information on land use changes in terms of the area and type of land use in the research area in 2010-2018. This research is focused in 3 (three) sub-districts in Kupang City. The reason for choosing the location is because observations show that there are many changes in land use, even areas that should not be used have experienced a touch of development. In addition, there are several educational centers, especially universities located in the area which tend to trigger land use changes. The research method used is survey method and data collection with SAS Planet Satellite Image Interpretation. The method of spatial analysis using GIS is by visual interpretation, digitization and overlay. Visual interpretation, digitization and overlay are used to determine land use changes that occur in the study area. The results in this study indicate that SAS Planet High Resolution Satellite Imagery can be used to identify land use information in Kupang City, because it can display objects more clearly, so that interpretation results can reach 90 percent accuracy and land use change analysis shows that within 8 years (2010-2018) there has been a significant change in land use where the built up land in the form of buildings, settlements and forests/mangroves has increased in area. Along with that, there is a reduction in the area of ​​use of grasslands and shrubs. Conversion of the fields also occurs in a moderate area. there was a significant change in which the highest land change occurred in the use of built-up land (buildings and settlements) and forests/mangroves, each of which experienced an increase of 108.45 ha (3.44 percent), settlements increased by 894.88 ha (27.50 percent) , and forest/mangrove area increased by 167.92 ha (5.16 percent).